Symbolic Resistance among Fishermen in Mekar and Bajo Indah Villages, Soropia District, Konawe Regency: A Critical Sociological Perspective - Pendais Haq; Abdul Sakti; La Ode Dinda; Adri (Journal of Law, Social Science and Management, 2025)
Background: The development of coastal tourism often produces ambivalent effects on local communities, particularly among traditional fishing populations. Objectives: This study aims to analyze the forms and dynamics of symbolic resistance that have emerged within fishing communities in Mekar Village and Bajo Indah Village, Soropia District, Konawe Regency, as a response to the pressures of tourism-driven development. Methods: Employing a qualitative approach with a case study design, data were collected through in-depth interviews with key informants from the fishing communities. Results: The findings reveal that the resistance manifested was predominantly non-confrontational, symbolic, and fragmented. Expressions of discontent were conveyed through passive actions, such as the deliberate absence from village meetings and the strategic use of social media platforms as spaces for articulating collective concerns. Local actors including youth and religious leaders played roles as mediators and facilitators of discourse, rather than as instigators of overt resistance. Furthermore, the communities articulated narratives of aspiration for more inclusive and equitable development, indicating not a wholesale rejection of tourism, but a critical engagement with its current forms. Conclusion: Symbolic resistance functions as a cultural strategy through which coastal communities strive to safeguard their identities, access to resources, and notions of social justice amid structural transformations induced by the tourism economy. This study contributes to the broader discourse on contemporary social movements in coastal regions.